Association between gender, socioeconomic status, blood pressure, Body Mass Index, and stroke in Germany: An analysis based on the Robert Koch-Institute survey data (DEGS) - Cedric Noune Tankou (2022)
Background: The number of deaths due to NCD has increased from 2007 to 2017 by 22.7% (CI: 21.5-23.9). This represents an additional 7.61 million (CI: 7.20-8.01) deaths estimated in 2017 versus in 2007. Classified under NCD, a group of heart and blood vessels disorders called CVD occupies the first postion. CVDs are the leading cause of death globally and are responsible for arround 40% of deaths in Germany. Ranking CVDs in terms of mortality, stroke appears at position two behind coronary artery disease. 243 000 to 260 000 persons in Germany suffer from stroke each year according to RKI. Several risk factors could lead to stroke, of which the modifiables like blood pressure and the nonmodifiable like gender are registered. Methods: Secondary data on the health status, health-related behavior, healthcare and living conditions of adults from the DEGS carried out by the RKI between 2008 and 2011 are used for a secondary analysis. The bivariate tests to assess the association between gender, blood pressure, BMI, SES, and stroke are mainly point-biserial correlation and chi-square, whereas a hierarchical multiple binary logistic regression analysis determines the predicting characters of these independent variables on the outcome stroke. Results: Gender (X² (1) = 13.154, p< 0.001), high blood pressure (males: X² (1) = 44.714; p< 0.001; females: X² (1) = 52.019; p< 0.001), SES as a score (males: r = 0.054; p=0.008; females: r = 0.094; p<0.001) are positively significantly associated with stroke, however BMI is not significantly associated to stroke for males (r = -0.024; p=0.241), but negatively significantly associated to stroke for females (r = -0.070; p<0.001). Hypertension (males: b = -1.124; CI: 0.185-0.570; p < 0.001; females: b = -1.464; CI: 0.099-0.538; p=0.001), low SES compared to middle SES (males: b = -0.600; CI: 0.319-0.944; p=0.030; females: b = -0.675; CI:0.271-0.956; p=0.036) are significant predictors of stroke, whereas high SES (males: b = 0.324; CI:0.789 - 2.422; p=0.257 and females: b = 0.997; CI:0.809-9.082; p = 0.106) compared to middle SES and centered BMI (male: b = 0.032; CI:0.975-1.094; p = 0.273; females: b = -0.019; CI:0.927-1.039 p = 0.511) are not. Discussion: The findings support the evidence that stroke depends on hypertension, score derived from SES for both males and females, BMI (for females) and gender, however, does not depends on BMI for males. Moreover, the predictors high blood pressure, low SES compared to middle SES had a significant influence on stroke for both genders, whereas BMI and high SES compared to middle SES had no influence on the outcome stroke.
Keywords: gender; SES; BMI; high blood pressure or hypertension; stroke; NCD